Tracing the dimension of non-duality in Mikhail Naimi’s The Book of Mirdad - Faisal, Hafiz Shahrear (Brac University, 2020)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Masters of Arts in Teaching to Speakers of Other Languages, 2019.